Analgesic activity of a novel use-dependent sodium channel blocker, crobenetine, in mono-arthritic rats - Laird, J M A (2001)
1. Although sodium channel blockers are effective analgesics in neuropathic pain, their effectiveness in inflammatory pain has been little studied. Sodium channels are substantially up-regulated in inflamed tissue, which suggests they play a role in maintenance of chronic inflammatory pain. We have examined the effects of sodium channel blockers on mobility, joint hyperalgesia and inflammation induced by complete Freund's adjuvant injected in one ankle joint of adult rats. The clinically effective sodium channel blocker, mexiletine, was compared with crobenetine (BIII 890 CL), a new, highly use-dependent sodium channel blocker. 2. Rats were treated for 5 days, starting on the day of induction of arthritis and were tested daily for joint hyperalgesia, hind limb posture and mobility. At post-mortem, joint stiffness and oedema were assessed. Dose response curves were constructed for each test compound (3 – 30 mg kg day(−1)). Control groups were treated with vehicle or with the non-steroidal anti-inflammatory drug, meloxicam (4 mg kg day(−1) i.p.). 3. Both sodium channel blockers produced dose dependent and significant reversal of mechanical joint hyperalgesia and impaired mobility with an ID50 of 15.5±1.1 mg kg day(−1) for crobenetine and 18.1±1.2 mg kg day(−1) for mexiletine. Neither compound affected the responses of the contralateral non-inflamed joint, nor had any effect on swelling and stiffness of the inflamed joint. 4. We conclude that sodium channel blockers are analgesic and anti-hyperalgesic in this model of arthritis. These data suggest that up regulation of sodium channel expression in primary afferent neurones may play an important role in the pain and hyperalgesia induced by joint inflammation.